2020
DOI: 10.29327/213319.20.1-28
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de lactentes expostos e não expostos ao HIV: estudo longitudinal

Abstract: RESUMO -Este estudo prospectivo de natureza longitudinal avaliou e comparou o desenvolvimento motor, cognitivo e da linguagem de lactentes expostos e não expostos ao HIV nos primeiros 12 meses de vida. Participaram 15 lactentes expostos ao HIV e a terapia antirretroviral (Grupo Experimental -GE) e 9 lactentes não expostos (Grupo Controle -GC). Foram avaliados o desenvolvimento motor, cognitivo e da linguagem nas idades de 4, 8, 12 e 18 meses de idade por meio da Bayley Scale of Infant and Toddler Development (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…The systematization and checklist of child assessment tools according to the ICF model act as guides to broaden and create reasoning that goes beyond body functions and structure in infants exposed to HIV. Research on neuropsychomotor development of infants at biological risk for HIV exposure using Bayley III, considering the cognitive, motor, and language domains, showed the influence that environmental factors have on functioning, i.e., a multidirectional interaction of the environment with the components of activity and participation and body structure and function act as facilitators or barriers in capacities and/ or deficiencies 9,16,17 . Moreover, studies assessing infants exposed to HIV showed lower scores in motor, cognitive, and language abilities up to 24 months of age when compared to those not exposed 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…The systematization and checklist of child assessment tools according to the ICF model act as guides to broaden and create reasoning that goes beyond body functions and structure in infants exposed to HIV. Research on neuropsychomotor development of infants at biological risk for HIV exposure using Bayley III, considering the cognitive, motor, and language domains, showed the influence that environmental factors have on functioning, i.e., a multidirectional interaction of the environment with the components of activity and participation and body structure and function act as facilitators or barriers in capacities and/ or deficiencies 9,16,17 . Moreover, studies assessing infants exposed to HIV showed lower scores in motor, cognitive, and language abilities up to 24 months of age when compared to those not exposed 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…This opposite result may be due to the fact that our study is cross-sectional. It is also worth noting that the study by Neves and Sá (2020) did not evaluate the home environment in which these infants were inserted, that is, it is not known how much stimulation this infant was exposed to, what the family condition is for the development of the infant, since it has been proven that home stimulation helps the infant's overall development (SILVA, SÁ, CARVALHO, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous studies that only evaluated the development of exposed and unexposed infants (SILVA, SÁ, CARVALHO, 2017;ALIMENT et al, 2006;NEVES & SÁ, 2020), the present study also evaluated the environment in which these infants were developing, and correlated that with their overall development, which makes this a pioneering study. Through the AHEMD questionnaire, significant Fine Motor Skills differences were found between the two groups, in which the SG presented better results than the CG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outros fatores de risco são a utilização da TARV e a contraindicação do aleitamento materno, já relatado por Ferreira et al (11) . O infante que se enquadra nessas características deve ser acompanhado em centros especializados de vigilância e ser submetido a testagens sorológicas até uma resolução de positivação ou não para o vírus HIV até os 18 meses de vida (12). Ademais, foi identificado no presente estudo que o nível da renda familiar se relaciona diretamente à rotina da família em realizar estímulos motores nas crianças avaliadas:…”
Section: Ure-mia O Acompanhamento Integral Dosunclassified